PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGHADAPI DAMPAK SOSIAL MEDIA TERHADAP AKHLAK SISWA DI SD MUHAMMADIYAH 18 PALEMBANG - Andika Apriansyah; Tutut Handayani; Amir Rusdi (Jurnal Genta Mulia, 2024)
As technology and information develop rapidly nowadays, there are many positive things that users, especially students, get. However, technology and information, in this case social media, have a negative effect on students, especially in their behavior. Students tend to imitate every deviant behavior that is accessed through social media. The aim of this research is to analyze the role of Pendidikan Agama Islam (PAI) teachers in dealing with the impact of social media on student morals at SD Muhammadiyah 18 Palembang. This research used a qualitative descriptive method by taking data from 2 PAI teachers and 9 students from grade 2 to grade 5 of elementary school. The results of the research show that the role of Pendidikan Agama Islam (PAI) teachers is felt to be very good in overcoming the negative effects of using social media among students at SD Muhammadiyah 18 Palembang.